Metaretorika Dakwah: Analisis Ceramah ‘Rutinan Malam Selasa’ Gus Iqdam - Hakim, Lukman; Mukhlis, Zainal; Pardianto (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2025)
This study explores the metarhetoric KH Muhammad Iqdam Kholid's, known as Gus Iqdam, sermons in